Circulation of a Simbu Serogroup Virus, Causing Schmallenberg Virus‐Like Clinical Signs in Northern Jordan. Issue 4 (30th December 2015) - Abutarbush, S. M.; La Rocca, A.; Wernike, K.; Beer, M.; AL Zuraikat, K.; Al Sheyab, O. M.; Talafha, A. Q.; Steinbach, F.
Summary: Schmallenberg virus (SBV)‐like clinical cases of abortions in northern Jordan in early 2013, together with the emergence of SBV in Europe in 2011, its rapid spread within the following years and the detection of this virus in Turkey, raised questions about the distribution of SBV or related orthobunyaviruses. To evaluate the occurrence of SBV or related members of the Simbu serogroup of orthobunyaviruses in Jordan, bulk milk (cattle) and serum samples (cattle, sheep and goat) collected in northern Jordan in 2013 were first tested by commercially available SBV antibody ELISAs. Indeed, 3 of 47 bulk milk samples and 57 of 115 serum samples provided positive results, but SBV specificity of the ELISA results could not be confirmed by virus neutralization assays. Instead, subsequent cross‐neutralization tests were able to further investigate the specificity of these antibodies. Here, a significant inhibition of Aino virus was observed. Thus, the causative agent was most likely a Simbu serogroup virus closely related to Aino virus. Consequently, these results confirm that members of this group of virus are not only present in Europe, Africa or Australia, but also in the Middle East.